PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEB PADA PT. GUNUNGMULIA DISTRIBUSINDO DENGAN METODE WATERFALL - NABILA SAFIRA (Himpunan Dosen Ilmu Komputer, 2023)
PT.Gunungmulia Distribusindo, which operates in the building materials distributor sector, currently has a manual data processing system using Microsoft Excel, both in recording goods inventory and goods purchase transactions and making goods inventory reports, so that many problems are faced, such as when making reports requiring This takes a lot of time so that the process is not effective and efficient, and it often happens that the data produced is inaccurate. It is necessary to design a computerized system that suits your needs so that it can be implemented. This research has analyzed and designed the system that runs at PT Gunungmulia Distribusindo using the waterfall method, while to help design the system modeling using UML. To collect documents as analysis material using interview methods and literature studies as theoretical references about the system to be designed. From this research, an inventory information system plan has been produced that has been adapted to the needs so that this plan can be used as a reference when building an inventory information system used by PT. Gunungmulia Distribusindo.